ORGAN DONATION AND TRANSPLANTATION COORDINATION IN THE SAMARA REGION: FEATURES OF THE REGIONAL MODEL - A. A. Mironov; B. I. Yaremin; A. V. Kolsanov; E. A. Gadlin; S. A. Snopov; V. I. Draznin; S. A. Kalyan; V. O. Bukanov; V. V. Grebennikov; V. T. Gashinskiy (Вестник трансплантологии и искусственных органов)
.